2011
DOI: 10.1007/s11120-011-9696-3
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituted CP29: multicomponent fluorescence decay from an optically homogeneous sample

Abstract: The multiexponential fluorescence decay of the CP29 complex in which the apoprotein and pigments were reconstituted in vitro was examined. Of the three decay components observed only the two dominant ones, with about 3 and 5 ns lifetimes, were studied. The main question addressed was whether the multicomponent decay was associated with sample optical heterogeneity. To this end, we examined the optical absorption and fluorescence of the CP29 sample by means of two different and independent experimental strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…1). A similar increase in fluorescence lifetime in detergent-solubilized antennae was shown for antenna complexes from higher plants or diatoms [26,30]; this was rationalized by antennae aggregation in vivo that is minimal in the detergent-solubilized system [26] or by antennae perturbations as a result of a detergent-aqueous environment [33,34]. Quenching of the antenna fractions was induced in vitro using a method described previously [35][36][37] (Fig.…”
Section: Npq In the Isolated Antenna Complexes Is Inhibited By Violaxsupporting
confidence: 60%
“…1). A similar increase in fluorescence lifetime in detergent-solubilized antennae was shown for antenna complexes from higher plants or diatoms [26,30]; this was rationalized by antennae aggregation in vivo that is minimal in the detergent-solubilized system [26] or by antennae perturbations as a result of a detergent-aqueous environment [33,34]. Quenching of the antenna fractions was induced in vitro using a method described previously [35][36][37] (Fig.…”
Section: Npq In the Isolated Antenna Complexes Is Inhibited By Violaxsupporting
confidence: 60%
“…Shown in Fig. 11 comparison of the calculated and measured absorption spectra 96 at room temperature. The absorption spectrum calculated at low temperature (77 K) is shown in Fig.…”
Section: Absorption Spectramentioning
confidence: 99%
“…Our findings suggest that the proposed extent to which closed RCIIs modulate the antenna chlorophyll lifetime should be reevaluated to account for the quenching effects of the proteolipidic membrane environment on the state of LHCII. In fact, it was previously shown that the LHCII fluorescence lifetime in liposomes at high protein/lipid ratios was not 4 ns, as for isolated trimers, but 2 ns (41), and an increasing number of studies are pointing to the effect of detergents on protein conformations, leading to different quenching states (42,43). It is therefore possible to consider that the 4 ns lifetime is an artificial condition that is induced by the detergent-aqueous environment and does not occur in vivo.…”
Section: The Chlorophyll Fluorescence Lifetime Of Lhcii-enriched Membranes Is Similar To That Of the Control In Both Light-harvesting Andmentioning
confidence: 99%